Customer Retention in Chinese Financial Retail Sector Quantitative Research in Shanghai - ZHANG, JIALE (2006)
The aim of the paper is to find out who the most profitable customers for domestic financial institutions to retain, and what those profitable customers preference when choosing simple/complex financial products. The database of 104 questionnaires collected in shanghai is used in the analysis. The result shows that the younger people (aged 35 years old or below) are those most profitable customers with great potential purchasing power on financial products. The result also confirms the differences of choosing criteria between simple financial products and complex financial products.